Mecanismos de fluorescência atrasada em polímeros conjugados - Paloma Lays dos Santos (2014)
In this work, we studied optical properties of two different groups of samples, which were made with the F8T2 copolymer (Poly(9,9-dioctylfluorene-alt-bithiophene)) and the P3HT polymer (Poly(3-hexylthiophene-2,5-diyl)) belonging to the first and second group, respectively. The samples were produced in two different ways: in diluted solutions and in films containing Zeonex®. The optical characterizations of the samples were performed by standard Optical Absorption, Photoluminescence and Photoluminescence Quantum Efficiency techniques. Other sophisticated techniques with temporal resolution namely Time Correlation Single Photon Counting Technique and measurements of Delayed Emissions and Phosphorescence using a sensitive gated iCCD camera (intensified Charge-Coupled Device) were also used. The measurements were performed as a function of the excitation laser intensity and/or as a function of temperature. We showed that the delayed fluorescence (DF) recorded for F8T2 samples originate from Thermally Activated Delayed Fluorescence mechanism (TADF) whereas it was origineted from Triplet-Triplet Annihilation mechanism for P3HT samples. Beyond the delayed fluorescence characterization, the phosphorescent emission spectra were also recorded for F8T2 and P3HT, which allowed us to make a complete study of the triplet states for these materials.